Evidence of taekwondo`s roots in karate: An analysis of the technical content of early taekwondo literature - Moenig, U.; Cho, S.; Kwak, T.-Y. (Korea Journal, 2014)
The taekwondo establishment presents taekwondo as the descendent of ancient Korean martial arts. However, during the last two decades, some scholars have begun to question this presentation, contending instead that taekwondo is the product of Koreans who studied karate in Japan during the Japanese colonial years, and then introduced karate to Korea after coming home. A comprehensive survey of the existing Korean martial arts literature published between 1945 and 1970 strongly supports the argument that early "taekwondo" had in fact been Japanese karate, or more specifically, Funakoshi Gichin`s Shotokan karate. Therefore, the assertion that early taekwondo had its roots in Korean martial arts is difficult to sustain.